2018
DOI: 10.1523/eneuro.0329-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Impairs Low-Frequency Feedback but Leaves High-Frequency Feedforward Connectivity Intact in the Fly Brain

Abstract: Hierarchically organized brains communicate through feedforward (FF) and feedback (FB) pathways. In mammals, FF and FB are mediated by higher and lower frequencies during wakefulness. FB is preferentially impaired by general anesthetics in multiple mammalian species. This suggests FB serves critical functions in waking brains. The brain of Drosophila melanogaster (fruit fly) is also hierarchically organized, but the presence of FB in these brains is not established. Here, we studied FB in the fly brain, by sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 81 publications
2
46
0
Order By: Relevance
“…To conclude, the spectral decomposition of integrated information we derived provides a new tool for investigating frequency-specific causal influences. This will be particularly useful for systems for which frequency-specific causal influences are masked in the time-domain, as increasingly reported in neural systems [13,14,18,41,42]. In particular, the spectral decomposition of integrated information we presented offers a new angle for empirically investigating the integrated information theory of consciousness [43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To conclude, the spectral decomposition of integrated information we derived provides a new tool for investigating frequency-specific causal influences. This will be particularly useful for systems for which frequency-specific causal influences are masked in the time-domain, as increasingly reported in neural systems [13,14,18,41,42]. In particular, the spectral decomposition of integrated information we presented offers a new angle for empirically investigating the integrated information theory of consciousness [43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 91%
“…For example, a number of studies have shown that transfer entropy from frontal to parietal brain areas is disconnected during unconsciousness as induced by various general anesthetics [15][16][17]. Recently, we have reported that general anesthesia reduces low-frequency feedback from the center to the periphery of the fly brain, while high-frequency feedforward in the opposite direction remained intact [18].…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila exposed to isoflurane demonstrate an uncoupling of neural activity patterns from movement at lower doses and cessation of movement at higher doses that correlate with local field potential characteristics [155]. More recent work in Drosophila has focused on hierarchical brain organization, assessing the effects of isoflurane anesthesia on higher-order central structures and lower-order peripheral structures [156]. As in mammalian brain systems, there were faster frequencies associated with feedforward directed connectivity (from lower-order to higher-order) and slower frequencies associated with feedback directed connectivity (from higher-order to lower-order).…”
Section: Network Effects Of General Anesthetics Across Speciesmentioning
confidence: 99%
“…To construct the IIS, we used local field potentials (LFPs; hereafter referred to as "channels") recorded from the fruit fly brain ( Fig 1A; see Methods; [11]). LFPs were recorded using a linear multi-electrode array, such that the 15 channels covered both peripheral and central regions of the brain.…”
Section: Constructing Integrated Information Structures From Fly Locamentioning
confidence: 99%
“…And third, can estimating the informational structures give us any biological hints as to the "interesting" regions of the brain that correlate with the level of consciousness? We address these questions by analyzing neural recordings from a simple biological system (fruit flies), collected during wakefulness and isoflurane anesthesia [11,21].…”
Section: Introductionmentioning
confidence: 99%